The Public Policy Implementation on the Merchants Relocation in Tebing Tinggi City, North Sumatera Indonesia (Research, Society and Development, 2020)
This research described the public policy implementation Mayor's Regulation of Tebing Tinggi City Number: 501/195 of 2018 through model of Van Meter and Van Horn concerning to the Relocation Merchants in Pasar Kain and Pasar Induk Market Tebing Tinggi. This research method applied the qualitative approach and descriptive analysis. To gain data and information some informant included the Head of the Trade Office, Merchants, Members of Legislative and the local non-governmental organizations were selected. According to the research and discussion, there were results of the implementation of the Pasar Kain merchant relocation policy. It show that the standards and policy objectives were adequate of clear and realistic to be implemented. The utilization of available resources was not used optimally, communication between organizations was adequate. In the beginning there are many miscommunications between merchants and the relocation team, the characteristics of the implementing organization were consistent despite the many conflicts of interest and internal conflicts among the social, economic and political environment.  In the initially, there were many social conflicts, the involvement of political elites and decrease income of merchants after being relocated. The attitude of the implementers was also quite consistent in supporting the policy. The implementation of the Pasar merchant relocation policy has not been optimal because the stalls have not been completely occupied.